Telaah Kritis Peran Jaringan Sosial Siti Rodliyah Dalam Pemilihan Legislatif 2009 Di Jepara - Aisyah Maulida; Kushandajani .; Susilo Utomo (Journal of Politic and Government Studies, 2014)
ABSTRACKAccording to the law No 10 tahun 2008, the last general election in 2009 had used the reasonable open general selection system. In this system, every legislatif member candidates were given a heavy responsibility to succed winning the selection with the votting system. Work hard was necessary done to interest the society sympathy so that they ready come to the voting booth in selection day. The campaign method that was used to build image more various like Siti Rodliyah did as a midwife in Tegalsambi village the subdistrict of Tahunan the regency of Jepara. Having capital of social media as a midwife, Siti Rodliyah succed getting 3.227 voices and became the highest voive from DPP PPP Dapil 1 Jepara, her proponent party.            In this research, the type of the research used was descriptive research that has objective to describe about the situation and phenomenon systematically, factual and accurate about the facts, included the process that happened and the impact of phenomenon that existed. This research was used to find the knowledge and  information as widespread as possible based on the object of the research at the certain moment.            The result of the research showed that  the social media of Siti Rodliyah in the general election 2009 had an important role in getting her voive. Her job as a midwife made her easier famous by society and became the good opportunity to campaign getting the voice.            To keep the social media continuously is needed a hard work in order that the society feel as a served person and can meet their needs. However, it is deeply regretted if the hard effort to keep this constitution will be defeated by money politic. Therefore, every politic actors and all of involved people also have responsibility to give education in making the society smart in politic.